Long‐term seizure outcome after epilepsy surgery in patients with mild malformation of cortical development and focal cortical dysplasia. Issue 1 (13th December 2018) - Veersema, Tim J.; Swampillai, Banu; Ferrier, Cyrille H.; van Eijsden, Pieter; Gosselaar, Peter H.; van Rijen, Peter C.; Spliet, Wim G. M.; Mühlebner, Angelika; Aronica, Eleonora; Braun, Kees P. J.
Summary: Focal cortical dysplasia (FCD) and mild malformation of cortical development (mMCD) are frequent histopathologic diagnoses in patients who undergo surgery for refractory epilepsy. Literature concerning surgical outcome in patients with mMCD, as well as its contrast with FCD, has been scarce. We studied 88 patients with a histopathologic diagnosis of isolated FCD (n = 57) or mMCD (n = 31), revised according to the latest International League Against Epilepsy (ILAE) guidelines, who underwent resective or disconnective surgery. Our findings suggest differences between mMCD and FCD in clinical presentation and surgical outcome after surgery. Patients with mMCD developed seizures later in life, and their lesions had a predilection for location in the temporal lobe and remained undetected by magnetic resonance imaging (MRI) more frequently. A diagnosis of mMCD has a less favorable surgical outcome. Still, 32% of these patients reached continuous seizure freedom (Engel class 1A) at a latest median follow‐up duration of 8 years, compared to 59% in FCD. A histopathologic diagnosis of mMCD, extratemporal surgery, and indication of an incomplete resection each were independent predictors of poor outcome.